2017
DOI: 10.1111/jssr.12482
|View full text |Cite
|
Sign up to set email alerts
|

Christian Identification and Self‐Reported Depression: Evidence from China

Abstract: The nexus between religion and mental health in the East has been understudied, where the coexistence of multiple religions calls for scholarly attention to religious identification. This article investigates the impact on self-reported depression of an individual's identification with Christianity in a non-Judeo-Christian and religion-regulating social setting. Taking advantage of the Chinese General Social Survey 2010, our empirical analyses suggest that people who explicitly identify with Christianity repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 86 publications
3
21
0
Order By: Relevance
“…The Chinese case is particularly worth mentioning. Religious affiliates in China feel less free and less in control of their life than non-affiliates, presumably because religious denominations are not socially sanctioned in the national political context (Hu et al 2017). However, this discount in SOC among affiliates is smaller than the otherwise large discount when I take out the mediating effects of religious action.…”
Section: Resultsmentioning
confidence: 93%
“…The Chinese case is particularly worth mentioning. Religious affiliates in China feel less free and less in control of their life than non-affiliates, presumably because religious denominations are not socially sanctioned in the national political context (Hu et al 2017). However, this discount in SOC among affiliates is smaller than the otherwise large discount when I take out the mediating effects of religious action.…”
Section: Resultsmentioning
confidence: 93%
“…For example, a group of studies showed that religious people, on some occasions, experience psychological problems such as spiritual struggles, depression, and religious doubt (Ellison et al 2013; Exline, Yali, and Sanderson 2000; Jasperse, Ward, and Jose 2012; Krause and Wulff 2004). Also, individuals who belong to a marginalized religion are exposed to cultural conflicts and thus are more likely to have depression (Hu et al 2017). Differing from the individual- and micro-level perspective of these studies, the present study further shows how the polarized configuration of the religious composition may be adversely related to individual health.…”
Section: Discussionmentioning
confidence: 99%
“…People who are stigmatized by other groups are likely to experience more stress and have fewer opportunities to obtain health and economic resources (Link and Phelan 2001). The adverse experiences in daily life—discrimination and prejudice—may be chronic stressors that can cause long-term dysfunction in physical and mental adjustment (Aneshensel 1992; Hu, Yang, and Luo 2017; Mezuk et al 2013; Taylor, Buunk, and Aspinwall 1990; Yang, Hu, and Schieman 2019). Second, religion-based social segregation may reach high levels in diverse contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Eskin et al [ 17 ] proposed that religiosity may lose its protectiveness in a culture where religious affiliation is compulsory or is normative. On the other hand, according to Hu et al [ 27 ], the protectiveness of a religion against psychological distress depends on the social status of the religion. In their study, Christians were found to exhibit worse depression symptoms compared to Buddhists and individuals with no religion.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Christians were found to exhibit worse depression symptoms compared to Buddhists and individuals with no religion. This led them to hypothesize that self-identification with a marginalized religion may be a psychological burden [ 27 ]. Therefore, we aim to examine whether different religious affiliations among college students in China are associated with overall suicidal behavior, suicide attempt, and suicide risk.…”
Section: Introductionmentioning
confidence: 99%